Adsorpsi Zat Warna Methylene Blue Menggunakan Karbon Aktif Kulit Kelengkeng (Euphoria longan lour) Dengan Metode Batch - Harmaiyani, Risky; Amran, Ali; Oktavia, Budhi; Kurniawati, Desy (Periodic, 2023)
In Indonesia, longan skin has not been widely used. Longan skin contains lignin which has good absorption ability. The cause of this research is to calculate the finest absorption capability of longan peel activated carbon against methylene blue dye using the batch method. The results confirmed that the optimum absorption ability for the absorption of methylene blue at pH 4, concentration of 600 ppm, and contact time of 120 minutes at a stirring speed of 200 rpm, and a mass of 0.2 grams was 69.0679 mg/g.